Detection of Vibrio sp. on vaname shrimp (Litopanaeus vannamei) cultivation pond in Gorontalo, Indonesia - PENI ULFIANI; ANI M. HASAN; YULIANA RETNOWATI (Nusantara Bioscience, 2022)
Abstract. Ulfiani P, Hasan AM, Retnowati Y. 2022. Detection of Vibrio sp. on vaname shrimp (Litopanaeus vannamei) cultivation pond in Gorontalo, Indonesia. Nusantara Bioscience 14: 340-346. Vibrio is a pathogenic bacteria that can attack cultured shrimp. Therefore, it is necessary to increase the intensity of water changes and efforts to control water quality to maintain dissolved oxygen levels and manage organic matter content in ponds to prevent the increase of pathogenic bacteria, especially Vibrio. In addition, water physicochemical factors can influence the presence and population of Vibrio bacteria in ponds. This study aims to determine the presence of Vibrio sp. in vaname shrimp culture ponds in Gorontalo, Indonesia. Descriptive quantitative analysis was used to analyze the data collected from this study. Shrimp pond water samples were obtained from shrimp ponds in Molosipat Village, West Popayato Sub-district, Pohuwato District, Gorontalo, Indonesia, using a purposive sampling technique with an interval of three days from the first water change to the last before the water change in one period (approximately 10 days). The water samples were subjected to physicochemical analysis, including temperature, pH, salinity, ammonia, nitrate, and dissolved oxygen. The results showed that there were Vibrio bacteria in the Thiosulfate Citrate BileSalt Sucrose Agar (TCBSA) medium with a population that tends to increase in the range of 1.0 × 103 - 2.7 × 104 CFU/mL. The isolation results showed that two isolates were named ISL1 and ISL2, with the colony morphology characters of ISL1 isolates being green and ISL2 isolates being yellow. The results of microscopic observations of the two isolates showed comma-shaped and gram-negative cells. Molecular identification using the 16S rRNA gene and reconstruction of the phylogenetic tree using the Neighbor-Joining algorithm showed that ISL1 isolate is very closely related to Vibrio parahaemolyticus strain 11-1 (relationship level 99%) and ISL2 is closely related to V. parahaemolyticus strain B2-1 (relationship level 86%).